Participatory ethnobotany and conservation: A methodological case study conducted with quilombola communities in Brazil's Atlantic Forest - Rodrigues, Eliana; Cassas, Fernando; Conde, Bruno Esteves; Da Cruz, Crenilda; Barretto, Eduardo Hortal Pereira; Dos Santos, Ginacil; Figueira, Glyn Mara; Passero, Luiz Felipe Domingues [UNESP]; Dos Santos, Maria Alice; Gomes, Maria Angélica Silva; Matta, Priscila; Yazbek, Priscila; et al. (Springer Nature, 2020)
Background: Although multiple studies advocate the advantages of participatory research approaches for ethnoscience, few provide solid contributions from case studies that involve residents in all of the project phases. We present a case study of a participatory approach whose aim is to register ethnobotanical knowledge on the use of plants in two quilombola communities (maroon communities), an important biodiversity hotspot in the Atlantic Forest, Southeast Brazil. Our aim is to provide tools that will empower decision-making related to sustainable use and management among residents. Methods: In phase I, the objectives and activities were defined in meetings with residents to carry out ethnobotanical surveys between two quilombola communities-the Quilombo da Fazenda (QF) and Quilombo do Cambury (QC). In phase II, we offered community partners training courses on how to collect plants and ethnobotanical data. In coordination with the university team and using ethnobotanical methods, community partners interviewed specialists on plants and their uses. In phase III, using the participatory mapping method, residents indicated plot locations and collected plants to calculate the Conservation Priority Index for native species recorded in phase II. Results: In 178 days of fieldwork, two community partners from the QF and three from the QC selected 8 and 11 respondents who reported 175 and 195 plant species, respectively, corresponding to 9 ethnobotanical categories. Based on requests from the local community, booklets and videos with these data were collaboratively produced. A large percentage of species were found to be of great conservation priority-82.1% in the QC and 62.5% in the QF. Virola bicuhyba, Cedrela fissilis, Plinia edulis, and Tabebuia cassinoides are the species most at risk and will be the focus of phase IV, when a participatory management plan will be carried out. Additionally, we present both challenges and opportunities with the hope that others can learn from our successes and failures. Conclusions: Our experience shows that it is possible to train community members who wish to document their knowledge to support the process of ensuring that local knowledge is highly regarded, further ensuring its perpetuation. In this context, the project may be of great interest to development programs in promoting community-based management strategies for useful plants.
Keywords: Atlantic forest; Conservation; Ethnobotany; Participatory management; Participatory research